Scientific Mapping of Research in Renal Nursing and Telehealth: A Bibliometric Study - Ahmad Padli Al Munjiha; Heni Marliany; Irpan Ali Rahman; Thandar Soe @ Sumaiyah Jamaludin; Henri Setiawan (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2026)
Background: This study aimed to evaluate scientific development, collaboration patterns, and emerging research trends in renal nursing and telehealth through a bibliometric analysis of PubMed-indexed publications from 2016 to 2026. Methods: A cross-sectional bibliometric approach was employed to analyze publication characteristics, annual growth trends, influential studies, collaboration networks, keyword co-occurrence, factorial analysis, and trend topics. Data were retrieved from PubMed and analyzed using bibliometric techniques to assess the intellectual structure and research evolution of renal nursing and telehealth. Results: A total of 28 publications from 24 sources were identified. The annual publication growth rate was ?4.94%, with an average of 12.46 citations per document and an international co-authorship rate of 14.29%, indicating moderate academic impact and limited global collaboration. The most cited studies focused on dialysis care, chronic kidney disease, telemedicine, telenephrology, home dialysis, and healthcare management during the COVID-19 pandemic. Network and factorial analyses revealed multidisciplinary research themes involving medicine, nursing, intensive care medicine, rehabilitation, mental health, psychological interventions, healthcare services, and digital health technologies. Trend topic analysis demonstrated increasing interest in telemedicine, remote patient monitoring, and digital healthcare approaches in renal nursing, particularly after the COVID-19 pandemic, which accelerated telehealth adoption worldwide. Conclusion: Research on renal nursing and telehealth has shown increasing scholarly attention over the past decade, with prominent themes including dialysis care, chronic kidney disease management, remote patient monitoring, and healthcare accessibility. The findings provide a comprehensive overview of the current research landscape and may serve as a reference for future bibliometric and empirical research in renal nursing and telehealth.